Pengaruh Kombinasi Nutris dan Naungan terhadap Pertumbuhan Selada dengan Sistem Hidroponik Vertikultur - Annisa Lailatus Sufiaah (Fakultas Pertanian, 2025)
Lettuce is widely favored by the Indonesian population because it contains nutrients that are good for the human body such as protein, fat, carbohydrates, Vitamin A, Vitamin B, and Vitamin C. Lettuce plants can be cultivated hydroponically. Factors that must be considered in the hydroponic system are nutrient content and environmental factors. The nutrient content used in the hydroponic system is AB Mix, because of its expensive use the solution that can be done is to use liquid organic fertilizer. Environmental factors that can affect the results of plant growth are sunshine. The use of shade is needed so that the atmospheric conditions around the environment are close to the optimum conditions of lettuce plants. This study used three levels of combinations, namely control 100% AB Mix, 25% POC, and 50% POC. While in the shade treatment using 6% and 14% UV plastic shade. Based on the research that has been done, it is found that the interaction between the combination of nutrients and shade affects the number of leaves, leaf width, and root volume of lettuce, but has no effect on plant height, and fresh weight of lettuce plants.
Entry oleh Arif 2026 Maret 05
Keywords: Lettuce; Liquid Organic Fertilizer; Shade; Vertical Hydroponic